“Isu Perempuan” (Dakwah dan Kepemimpinan Perempuan dalam Kesetaraan Gender) - Dewi Sa’diyah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2008)
Dakwah can be done by anyone according to their abiliities. The duty in Islam, that is not only for men but is also for women. Islam does’nt differenciate between men and women in doing good deeds, they are the same in beside God. The problems, there is more prejudise or mythos and act lower to women. The fact, in cassues, treatment injustice in taking role in public sectors, whereas in other places and in history, women also have enough skill in leadership.